EFFICACY AND LONG-TERM STABILITY OF ZIRCONIUM DIOXIDE-BASED ALL-CERAMIC CROWNS IN CLINICAL APPLICATION - Rajabova Mohira Ergashovna (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
ANNOTATION: The development of high-strength ceramic materials has revolutionized fixed prosthodontics, with zirconium dioxide (zirconia) emerging as a leading material for all-ceramic crowns due to its exceptional mechanical properties and biocompatibility. This study aims to evaluate the clinical efficacy and long-term stability of zirconium dioxide-based all-ceramic crowns through a systematic review of clinical studies and meta-analysis of survival rates.